Ingalik material culture - Osgood, Cornelius, 1905- (New Haven, Pub. for the Department of anthropology, Yale university, by The Yale university press; London, H. Milford, Oxford university press, 1940)
Bibliography: p. 485-487. Mode of access: Internet.